Different aspects of laboratory analog of tropical cyclone. (February 2019) - Sukhanovskii, A; Evgrafova, A; Pavlinov, A; Popova, E; Shchapov, V.
Abstract: Localized heating in the rotating layer of fluid leads to the formation of intense cyclonic vortex. Cyclonic vortex becomes unstable at low values of viscosity and fast rotation of the experimental model. The instability of the vortex is tightly connected with a structure of the radial inflow. For moderate values of rotational Reynolds number Re the radial flows consist of several branches which transport angular momentum to the center of the model. When Re exceeds critical value (about 23) radial inflow changes its structure and appears as one wide branch which does not reach the center. As a result of strong anisotropy of radial inflow the cyclonic vortex is formed at some distance from the center. Further increase of Re leads to chaotic state with several vortices which appear at different locations near the periphery of the heating area. The map of regimes with stable and unstable vortices is presented.